Oxa-Michael-initiated cascade reactions of levoglucosenone - Klepp, Julian; Bousfield, Thomas; Cummins, Hugh; Legendre, Sarah V. A.-M.; Camp, Jason E.; Greatrex, Ben W. (Beilstein Journal of Organic Chemistry, 2022)
The reactions of aromatic aldehydes and levoglucosenone promoted by methoxide gives bridged α,β-unsaturated ketones, formed by a series of oxa-Michael-initiated cascade reactions in yields of up to 91% (14 examples). A complex series of equilibria operate during the reaction, and the formation of the bridged species is thermodynamically favored, except in the case of 5-methylfurfural and pyrrole-2-carboxaldehyde. This is the first report detailing this type of aldol/Michael cascade involving oxa-Michael initiation.
Keywords: cascade reactions; green chemistry; levoglucosenone; oxa-Michael reaction